Faktor- Faktor Yang Memengaruhi Produksi ASI Pada Ibu Menyusui 0- 6 Bulan Di Wilayah Kerja Puskesmas Bangetayu - Tutik Rahayu; Istiadhatul Arzakiyah; Apriliani Yulianti W (Indonesian National Nurses Association (INNA) of Central Java, 2020)
Background: Breast milk is food that is given to babies that is released directly from the mother's breast and contains several nutrients according to the needs of the baby as an antibody. There are several factors that affect milk production. Purpose: This study aimed to determine the factors that influence milk production in nursing mothers 0-6 months.Methods: This type of research is cross sectional .. The number of respondents was 105 people with consecutive sampling technique. The data obtained were processed statistically using multiple logistic regression statistical tests.Result: The results showed that the majority of respondents had multipara parity status of 58.1%, mothers did not work as much as 76.2%, used hormonal contraception as much as 65.7%, did regular breast care as much as 57%, age was not rested as many as 86, 7%, 51.4% IMD, 53.3% giving pralacteal food, 67.6% adequate breastfeeding frequency, 92.4% insufficient nutritional status, 53.3% pathological delivery, breastfeeding technique 67.6% less, higher education 68.6% and high family income 51.4%. Statistical test results show that the actor who most influences the production of breast milk in nursing mothers 0-6 months is IMD with an OR value of 3,469.Conclusion: There is an influence of parity status, contraceptive use, breast care, BMI, pralacteal feeding, frequency of breastfeeding and breastfeeding techniques on milk production. The most influential factor is IMD.